Two new species of Hohenbuehelia (Pleurotaceae) from China - Qi, Liangliang; Ge, Yupeng; Li, Liying; Qin, Yanchun; Zeng, Hui; Lang, Ning; Li, Yu (Phytotaxa, 2023)
Only two species of Hohenbuehelia, a globally distributed genus, are present in subtropical and tropical areas of China. Here, we describe and illustrate two additional subtropical species of Hohenbuehelia from Guangxi Province. Hohenbuehelia longzhousis can be differentiated from similar Hohenbuehelia species by its large size and its flesh- to pale-flesh-surfaced basidiomata, whereas H. cepistipes can be distinguished by its unique sturdy, thick stipe, an undulating to wavy margin of pileus. On the basis of morphology, the two species are distinct from all other species in the genus, which is a conclusion also strongly supported by the results of a phylogenetic analysis. Images of the original habitats and microstructures of the two new species are presented, and a revised taxonomic key for Chinese Hohenbuehelia is provided.